2014
DOI: 10.1007/s10549-013-2825-2
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of the conversion rate in the receptor status between primary breast cancer and metastasis: results from the GEICAM 2009-03 ConvertHER study

Abstract: The objective of this study was to determine the conversion rate of human epidermal growth factor receptor 2 (HER2), estrogen receptor (ER) and progesterone receptor (PR) between primary tumors and metastatic lesions in advanced breast cancer. Patients with suspected diagnosis of locally recurrent or metastatic breast cancer, either at first relapse or after successive disease progressions, who had an appropriately preserved sample from a primary tumor and were scheduled for a biopsy of the recurrent lesion, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 14 publications
8
50
1
1
Order By: Relevance
“…We found that 34% of ER conversion and 17% of PR conversion could be due to technical misclassification. This finding is in line with a recent prospective study showing that the conversion rate for ER was 21% in local laboratories and 13% in a central laboratory (38% relative reduction) and that the conversion rate for PR was 35% and 28% in local and central laboratories, respectively (i.e., 20% relative reduction) [25]. After correcting for misclassification, less than 3% of primary tumor and metastatic pairs showed a negative-to-positive receptor change.…”
Section: Discussionsupporting
confidence: 90%
“…We found that 34% of ER conversion and 17% of PR conversion could be due to technical misclassification. This finding is in line with a recent prospective study showing that the conversion rate for ER was 21% in local laboratories and 13% in a central laboratory (38% relative reduction) and that the conversion rate for PR was 35% and 28% in local and central laboratories, respectively (i.e., 20% relative reduction) [25]. After correcting for misclassification, less than 3% of primary tumor and metastatic pairs showed a negative-to-positive receptor change.…”
Section: Discussionsupporting
confidence: 90%
“…Prospective studies that include central review of all pathology have estimated the prevalence of the discordance of ER and HER2 receptor status between the primary and metastatic site to be 10-13% and 3%, respectively, notably lower than when assessed locally. 40,41 Of note, in these studies 8-10% of tested samples showed loss of ER expression, compared to 2-3% with a gain in ER; HER2 gain occurred slightly more frequently than HER2 loss (2-3% compared to 0-1%, respectively), 40,41 although other analyses found HER2 loss and gain to occur at a similar frequency. 42,43 The clinical implications of this change in receptor status are less well understood.…”
Section: Changing Biomarker Statusmentioning
confidence: 81%
“…This study was commenced in March 2010 and since then other studies have shown that tamoxifen dose escalation can lead to an increase in endoxifen level (27)(28)(29)(30). However, our study is notable as dose escalation occurred regardless of CYP2D6 genotype, and medications that were known to inhibit CYP2D6 metabolism were not an exclusion criteria allowing independent assessment of these factors.…”
Section: Discussionmentioning
confidence: 95%